A CASE STUDY ON INLAND WATER TRANSPORTATION SYSTEM IN KOCHI CITY REGION - Praveen S; Rajakumar S; Bhagavathi Pushpa T; Jegan J (International Journal For Technological Research In Engineering, 2015)
The authors explore to highlight the problems ailing the water transportation sector in Kochi. It relies upon extensive review of secondary data, observations about the ferry system recorded through various secondary survey reports, and perception studies to suggest feasible measures towards addressing those problems. The authors seek to highlight many hurdles faced by the people for whom the water transportation system of Kochi is meant. The authors end with suggestions to make water-based travel more appealing to the average user of various modes of transportation in Kochi City Region.